Implications of the 'happy-performing managers' proposition - Hosie, Peter; Sevastos, Peter; Travaglione, T. (2006)
A seminal question in industrial/organisational psychology and management is revisited in this paper - do happy managers perform better than their miserable counterparts? The 'happy-productive worker' thesis has intrigued organisational researchers and practitioners for decades. Despite mixed empirical evidence from research, there is support in the literature for the notion that 'a happy worker is a good worker'. A variation on the enduring debate of the happiness-productivity theme is presented - the 'happy-performing managers' proposition. A study of Australian managers is reported to illustrate how aspects of affective wellbeing are associated with their performance. The emphasis was on investigating an aspect of human behaviour with the potential to enhance managerial performance. A contribution of this study was to provide qualified support for the 'happy-performing managers' proposition by linking managers' affective wellbeing and intrinsic job satisfaction with their contextual and task performance. Implications of these findings are considered. In particular, it is argued that the capacity of managers to develop emotional intelligence, so that they are more aware of the importance of positive and negative leadership styles has the potential to increase organisational productivity.